The phytochemical and pharmacological profile of taraxasterol - Jiao, Fengjuan; Tan, Zengyue; Yu, Zhonghua; Zhou, Bojie; Meng, Lingyan; Shi, Xinyue (Frontiers in Pharmacology, 2022)
Taraxasterol is one of the bioactive triterpenoids found in dandelion, a member of the family Asteraceae. In the animal or cellular models of several ailments, including liver damage, gastritis, colitis, arthritis, pneumonia, tumors, and immune system diseases, taraxasterol has been shown to have significant preventive and therapeutic effects. This review aims to evaluate the current state of research and provide an overview of the possible applications of taraxasterol in various diseases. The reported phytochemical properties and pharmacological actions of taraxasterol, including anti-inflammatory, anti-oxidative, and anti-carcinogenic properties, and its potential molecular mechanisms in developing these diseases are highlighted. Finally, we further explored whether taraxasterol has protective effects on neuronal death in neurodegenerative diseases. In addition, more animal and clinical studies are also required on the metabolism, bioavailability, and safety of taraxasterol to support its applications in pharmaceuticals and medicine.